The gifts of imperfection - Brown, Brene (New York Random House, 2020)
For over a decade, Bren B̌rown has found a special place in our hearts as a gifted mapmaker and a fellow traveller. She is both a social scientist and a kitchen-table friend whom you can always count on to tell the truth, make you laugh and, on occasion, cry with you. And what's now become a movement all started with The Gifts of Imperfection, which has sold more than two million copies in thirty-five different languages across the globe.
Includes bibliographical references
Keywords: Self-acceptance.